PENGARUH PPH TERHADAP HADIAH, DISKON DAN INSENTIF - BRYNA ALVIANA, ELISSE Bryna A (Jurnal Akuntansi AKUNESA, 2012)
This study aims to see the impact of VAT on the provision of gifts, discounts and incentives. Associated with several tax provisions regarding imposition of income tax, income tax on lottery prizes and promotional expenses can be deducted on the gross income. This study uses a literature study of documents and tax law. Methods of analysis of this research uses descriptive method. This study used data from the literature and some of the tax law. Based on this study, the results show the influence of Tax on gifts, discounts and incentives are viewed from both sides, namely the giver and receiver Keywords : VAT, gifts, discount, incentives, influence of Tax